Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 6 - Algebra: Equations and Inequalities - 6.1 Algebraic Expressions and Formulas - Exercise Set 6.1: 34

Answer

0

Work Step by Step

$\frac{(2x+y)}{(xy-2x)}$, x=-2, y=4 Step 1:Substitute x=−2 and y=4 for each x and y $\frac{2(-2)+4}{(-2)(4)-2(-2)}$ Step 2: Multiply 2(-2) = -4 , (-2)(4) = -8 and 2(-2) = -4 $\frac{-4+4}{(-8)+4}$ Step 3: Add and subtract from left to right. $\frac{0}{-4}$ = 0
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.